Pengaruh Kompetensi Sumber Daya Manusia dan Penerapan Teknologi Informasi terhadap Kualitas Laporan Keuangan Sekretariat DPRD Kabupaten Maros - Tri Fira Yuniza; Anna Ashrawi Suhartini; Basri, Basri (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
The aim of this research is to determine and analyze the influence of competency and application of information technology on the quality of financial reports of theMaros Regency DPRD Secretariat partially and simultaneously. This type of research uses a quantitative descriptive approach with a population that will be sampled as 65 people, with a withdrawal technique. The sample uses a saturated sample, that is, the entire population will be used as a sample of 65 people. The analytical method used is multiple linear regression analysis with hypothesis testing using the partial t test, simultaneous F test and determination test (R2). The research results obtained are (1) Competency has a positive and significant influence on the quality of financial reports of theMaros Regency DPRD Secretariat, (2) Application of Information Technology has a positive and non-significant influence on the quality ofMaros Regency DPRD Secretariat's financial reports, (3) Competency and application of Information Technology in general Simultaneous Positive and Significant Influence on the Quality of Financial Reports of theMaros Regency DPRD Secretariat. Competence has a dominant influence on the quality of theMaros Regency DPRD Secretariat's financial reports.